(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: Hypertension is one of the leading causes of global burden of disease. In a study, prevalence of hypertension in India was quoted 13.1% and only 16.7% of the person had achieved BP control of 140/90mm Hg. Peripheral vascular disease (PVD) is a slow and progressive circulation disorder which is characterized by narrowing of the vessels that carry blood to the leg and arm muscles. It is estimated that PAD affects 2 billion people worldwide. It is also estimated that of all the hypertensives at presentation, 2-5% have claudication. Similarly 50-92% of patients with PAD have hypertension. The Ankle-brachial Index (ABI) is the ratio of the systolic blood pressures between the dorsalis pedis and the posterior tibial artery to the higher of the systolic blood pressures in the two brachial arteries. The ABIs sensitivity is 90% and its specificity is 98%. Normal ABI range of 1.00 to 1.40.The patient is diagnosed with PAD when the ABI is ? 0.90, ABI Acts as an independent predictor of coronary and cardiovascular morbidity and mortality. Materials and methods: In this study 100 patients were registered who were suffering from hypertension, which include both indoor and outdoor patients, were studied. These patients were between the age group 45-75 years. In this study 82 were males and 18 were females. .Patients with history of Diabetes, Smoking, Hyperlipidemia, and with other risk factors excluding hypertension were excluded from the study. Ankle Brachial Index (ABI) was measured for the patients. A Doppler ultrasound blood flow detector and a sphygmomanometer (blood pressure cuff) was used to measure ABI. The patient is diagnosed with PAD when the ABI is ? 0.90 Observation: Total number of patients 100. Prevalence rate of peripheral arterial disease in hypertensive patients with age group (45-75) was 7%. The highest prevalence rate was seen in patients in age group 65-75 years. Males had slightly higher prevalence of peripheral arterial disease than females. Prevalence of ECG abnormalities suggesting cardiovascular disease was higher in patients with peripheral arterial disease than patients without peripheral arterial disease. Abnormal ABI (<0.9) was found in significantly higher proportion of patients with clinical evidence of peripheral arterial disease (86%) than in patients without clinical evidence of peripheral arterial disease (1.1%). Conclusion: The present study shows that ABI is a valuable method for the diagnosis of peripheral arterial disease in patients of Hypertension and should be applied in routine practices which may improve cardiovascular risk prediction Bangladesh Journal of Medical Science Vol.15(4) 2016 p.556-564